Pengaruh Faktor Kepribadian dan Komitmen Organisasional terhadap Perilaku Peran Ekstra atau OCB (Organizational Citizenship Behavior) di SMK Pelita Nusantara 1-2 Semarang - Tasriastuti, Nurrohmi Ambar (Jurnal Ilmiah Fokus Ekonomi, Manajemen, Bisnis & Akuntansi (EMBA), 2022)
Personality is a dynamic organization in the individual's psychophysiological system that determines how he uniquely adapts to his environment. Organizational commitment is an active relationship between individuals and the organization which includes identification, involvement and loyalty, which are shown by individuals to their work units. No exception in organizations in educational institutions, also need workers who act beyond their job descriptions and duties. One of the keys to the successful implementation of education in the era of autonomy and globalization is the extent to which individuals in institutions are synergistically able to contribute positively, both in planning and in the process of implementing duties and responsibilities as members of the institution to achieve goals and create a quality generation. This study aims to analyze the influence of personality and organizational commitment on extra-role behavior or OCB at SMK Pelita Nusantara 1-2 Semarang. The primary data obtained from the questionnaires that were entered and were suitable for use as samples were 97 respondents. The analytical method used in this quantitative study is the classical assumption test and multiple regression testing and hypothesis testing using the t test and F test. The results show that there is a positive and significant influence of personality and organizational commitment, either partially or simultaneously, against OCB. For this study, the variable that has the dominant influence on OCB is the organizational commitment variable. Through the model designed for this research, the coefficient of determination (R²) is 0.536. This shows that 53.6% of the OCB variables can be explained by personality and organizational commitment variables, and the remaining 46.4% is explained by other variables outside this research model.Keywords: Personality, Organizational Commitment, OCB